Minat Siswa Dalam Pembelajaran Menulis Pada Siswa Kelas VIII SMPN 13 Tarakan - Riyant, Asih; Damayanti, Alfina; Magefira, Magefira; Sari, Arelia Yopita; Devin, Devin; Akbar, Yasin (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to understand the process of evaluating students' interest in learning to write in class VIII of SMPN 13 Tarakan. The method used is descriptive qualitative, with data collection through direct interviews in the field on Saturday, April 19, 2025. Data were collected using questionnaires, observation, and documentation. The researcher involved five respondents, namely an Indonesian teacher and four grade VIII students. The results showed that the teacher had carried out the evaluation process in learning to write well. Teachers conduct evaluation at the beginning, middle, and end of learning, according to the correct order. This helps students to understand the linguistic rules and achieve the learning objectives of writing. In delivering the material, the teacher mostly uses the lecture method. The aspects that become the focus of evaluation in students' writing include the use of punctuation, capital letters, and SPOK structure. In addition, the teacher applies three evaluation techniques in the learning process, namely diagnostic, formative, and summative evaluation.